Upper-band chorus wave observations during the closest conjunction of Van Allen Probe B and Arase spacecraft - Alwin Roy; Dedong Wang; Yoshizumi Miyoshi; Huiting Feng; Miroslav Hanzelka; Xiaoyu Wang; Xingzhi Lyu; Bernhard Haas; Haobo Fu; Ondrej Santolik; Yoshiya Kasahara; Shoya Matsuda; et al. (Advances in Space Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Leverage-based nutrient governance for drinking water sources using hydro-ecological zoning and source apportionment in the Yangtze River Basin - Haizhen Hu; Qing Fu; Sheng Chang; Yinying Zhu; Asaad Y. Shamseldin; Fan Zhang; Guang Yang; Chun Ye; Yueting Fan; Enrui Wang (Journal of Environmental Chemical Engineering, 2026)

Transformation and transport: Polyvinyl chloride microplastics modulate fipronil accumulation and toxicity in zebrafish - Long Fu; Jing Yu; Kunting Li; Peibin Xu; Keran Xu; Lei Mai; Dali Wang; Huizhen Li; Jing You; Eddy Y. Zeng (Journal of Environmental Sciences, 2026)

Neuromuscular control mechanism during posture-cognition dual task in mild cognitive impairment: a concurrent fNIRS-sEMG-COP study - Ruochen Fu; Jinjin Ma; Yao Zu; Yingying Fang; Yan Li; Arnold Y. L. Wong; Xue Cheng; Yan Leng; Jiajia Yang; Chuhuai Wang; Qiuhua Yu (GeroScience, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Environmental behaviors, biotransformation, and toxicological risks of PFPiAs: A comprehensive review of an emerging PFAS - Xihua Wang; Qinya lv; Y. Jun Xu; Rongbing Fu; Yueqing Xie; Chaomeng Dai; Nianqing Zhou; Yaqiang Wei; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu (Science of The Total Environment, 2025)

Effect of fetch on street canyon flow field and pollutant dispersion - Daniel Ziyue Peng; Bingchao Zhang; Yunfei Fu; Xisheng Lin; Wenke Li; Tim K.T. Tse; Cruz Y. Li (Building and Environment, 2025)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

Mapping the landscape of bird strike research: insights from a quantitative analysis - H. X. Wang; W. Fu; N. A. Razak; Y. Y. Shi (International Journal of Environmental Science and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

R&D investment and corporate total factor productivity under the heterogeneous environmental regulations: evidence from Chinese micro firms - X. Ding; Y. Zhang; Y. Fu; Z. Xu (International Journal of Environmental Science and Technology, 2025)

Perspective of explosive cyclones with three shapes of upper-level potential vorticity over the northern Atlantic Ocean - J. Ni; G. Fu; L. J. Chen; P. Y. Li (Climate Dynamics, 2025)

Unveiling the molecular mechanisms of adzuki bean (Vigna angularis) derived bioactive phytochemicals in combating obesity - Jinhai Luo; Yingzi Wu; Ashaimaa Y. Moussa; Yanyi Huang; Yu Fu; Yun Wei; Jincan Luo; Baojun Xu (Food Bioscience, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An Expanded National Database for Natural Product Use and Interaction Assessment - Y. Fu; T. Feinberg; E. Dennis (Journal of the Academy of Nutrition and Dietetics, 2024)

P10-08 Evaluation of real-life PFAS mixture toxicity and impact on 3D placenta spheroid model - Y. Xia; Q. Fu; H. Voss; S. Fest; A.C. Zenclussen; V. Stojanovska (Toxicology Letters, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Genetics and metabolic responses of Artemisia annua L to the lake of phosphorus under the sparingly soluble phosphorus fertilizer: evidence from transcriptomics analysis - Lingyun Wan; Juan Huo; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Mohamed A. Abd Elhamid; Salma A. Soaud; Rania M. Y. Heakel; Jihai Gao; et al. (Functional & Integrative Genomics, 2024)

A new discovery of 423.6 Ma Hongbaoshan gabbro in the Beishan area, NW China, and its geological significance - Y. G. Fu (Australian Journal of Earth Sciences, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Effects of Water Saturation and Loading Condition on Rock Tensile Strength: Insights from Acoustic Emission Analysis - Jun Zhu; Jianhui Deng; Po Ning; Ziguo Fu; Xuankun Li; Ronald Y. S. Pak (Rock Mechanics and Rock Engineering, 2024)

16s-RNA sequencing analysis of the influence of UV radiation on the metabolic pathways of pollutants in the A2O process - Y. W. Li; J. H. You; Y. C. Zong; J. Wang; C. H. Fu (International Journal of Environmental Science and Technology, 2023)

Histological, Physiological and Biomechanical Effects of Low-Level Laser Therapy on Tendon Healing in Animals and Humans: A Systematic Review - Kexu He; Xuelian Zhou; Feisheng Zheng; Xiaojie Ju; Siu-Ngor Fu; Arnold Y. L. Wong (Annals of Biomedical Engineering, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Relating critical and limiting fluxes to metastable and long-term stable fluxes in colloidal membrane filtration through collision-attachment theory - Junxia Liu; Wei Fu; Xuri Yu; Haiyan Yang; Dongsheng Zhao; Zhihong Wang; Lin Wang; Xianhui Li; Chuyang Y. Tang (Water Research, 2023)

Streamflow and sediment load changes from China's large rivers: Quantitative contributions of climate and human activity factors - Shihua Yin; Guangyao Gao; Anqi Huang; Dongfeng Li; Lishan Ran; Muhammad Nawaz; Y. Jun Xu; Bojie Fu (Science of The Total Environment, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Data-driven ESG assessment for blockchain services: A comparative study in textiles and apparel industry - Xinlai Liu; Yu Yang; Yishuo Jiang; Yelin Fu; Ray Y. Zhong; Ming Li; George Q. Huang (Resources, Conservation and Recycling, 2023)

Long-term trends of streamflow, sediment load and nutrient fluxes from the Mississippi River Basin: Impacts of climate change and human activities - Shihua Yin; Guangyao Gao; Yanjiao Li; Y. Jun Xu; R. Eugene Turner; Lishan Ran; Xiaofeng Wang; Bojie Fu (Journal of Hydrology, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

Effects of environmental factors on release amount of heavy metal and structure of microbial community in sediments - T. Wen; H. Zhong; G. Fu; Y. Zhong (International Journal of Environmental Science and Technology, 2022)

Failure modes of slope stabilized by frame beam with prestressed anchors - J. J. Zhang; J. Y. Niu; X. Fu; L. C. Cao; S. J. Yan (European Journal of Environmental and Civil Engineering, 2022)

Characteristics and formation mechanisms of Mesozoic compressional structures in the Huanghua Depression, Bohai Bay Basin, China - W. Li; F. Zhang; Y. Zhang; L. Fu; H. Li (Australian Journal of Earth Sciences, 2021)

Robust Estimation Procedure for Autoregressive Models with Heterogeneity - A. Callens; Y.-G. Wang; L. Fu; B. Liquet (Environmental Modeling & Assessment, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Modeling Coral Bleaching Mitigation Potential of Water Vertical Translocation – An Analogue to Geoengineered Artificial Upwelling - Ellias Y. Feng; Yvonne Sawall; Marlene Wall; Mario Lebrato; Yao Fu (Frontiers in Marine Science, 2020)
Artificial upwelling (AU) is a novel geoengineering technology that brings seawater from the deep ocean to the surface. Within the context of global warming, AU techniques are proposed to reduce sea surface temperature at times of thermal stress around coral reefs. A computationally fast but coarse 3D Earth System model (3.6° longitude × 1.8° latitude) was used to investigate the environmental impacts of hypothetically implemented AU strategies in the Great Barrier Reef, South China Sea, and Hawaiian regions. While omitting the discussion on sub-grid hydrology, we simulated in our model a water translocation from either 130 or 550 m depth to sea surface at rates of 1 or 50 m 3 s –1 as analogs to AU implementation. Under the Representative Concentration Pathway 8.5 emissions scenario from year 2020 on, the model predicted a prevention of coral bleaching until the year 2099 when AU was implemented, except under the least intense AU scenario (water from 130 m depth at 1 m 3 s –1 ). Yet, intense AU implementation (water from 550 m depth at 50 m 3 s –1 ) will likely have adverse effects on coral reefs by overcooling the surface water, altering salinity, decreasing calcium carbonate saturation, and considerably increasing nutrient levels. Our result suggests that if we utilize AU for mitigating coral bleaching during heat stress, AU implementation needs to be carefully designed with respect to AU’s location, depth, intensity and duration so that undesirable environmental effects are minimized. Following a proper installation and management procedure, however, AU has the potential to decelerate destructive bleaching events and buy corals more time to adjust to climate change.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Use of Microfluidics to Fabricate Bioerodable Lipid Hybrid Nanoparticles Containing Hydromorphone or Ketamine for the Relief of Intractable Pain - Minze Zhu; Andrew K. Whittaker; Xingyu Jiang; Rupei Tang; Xuanyu Li; Weizhi Xu; Changkui Fu; Maree T Smith; Felicity Y Han (Pharmaceutical Research, 2020)

Specific genes and sequence variation in pathotype 7 of the clubroot pathogen Plasmodiophora brassicae - H. Yang; J. Zheng; Y. D. Fu; Y. H. Zhang; C. L. Yi; C. Jin; Y. Huang; Wenming Wang (European Journal of Plant Pathology, 2020)

Petrogenesis of Jurassic Xietongmen intrusive rocks at the southern margin of the Lhasa terrane: implications for intra-oceanic arc evolution - Y. G. Fu; G. Y. Hu (Australian Journal of Earth Sciences, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Characteristics changes in banana peel coagulant during storage process - Y. Fu; X. J. Meng; N. N. Lu; H. L. Jian; Y. Di (International Journal of Environmental Science and Technology, 2019)

Evaluation of Stripe Rust Resistance in Hungarian Winter Wheat Cultivars in China - D. Huang; H. Zhang; M. Tar; Y. Zhang; F. Ni; J. Ren; D. Fu; L. Purnhauser; J. Wu (Cereal Research Communications, 2019)

Sequence stratigraphy and Quaternary depositional systems in the Sanhu area of the Qaidam Basin, northwest China - Z. Liu; S. Fu; H. C. Jia; J. X. Tian; Y. H. Chen; C. Y. Dong (Australian Journal of Earth Sciences, 2019)

Response Mechanism of Oviposition and Relevant Protein Expression of Bactrocera cucurbitae (Coquillet) to Short-Term High-Temperature Conditions - B Zeng; W Zhu; Y Fu; S Zhou (Neotropical Entomology, 2019)

Profiling of nuclear copper-binding proteins under hypoxic condition - Haiying Fu; Xueqin Ding; Wenjing Zhang; Y. James Kang (BioMetals, 2019)

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Synthesis, Characterization, and Application of a New Magnetic Silica Composite Nanoadsorbent with NiFe-Embedded Structure - Lei Fu; Y. Liu; Pan Huang; Xiaoyi Shen (Water, Air, & Soil Pollution, 2018)

Sequence subdivision and development characteristics of low-accommodation non-marine basins: a case study of the Yanchang Formation in the Ordos Basin - S. Fu; Z. Liu; Y.-Z. Li; Y.-R. Guo; X.-M. Xu; J.-J. Liu; X. D. Hu (Australian Journal of Earth Sciences, 2018)

Isometric strength of the hip abductors and external rotators in athletes with and without patellar tendinopathy - Z. J. Zhang; W. C. Lee; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Self-assembled microspheres feasibility study for conformance control in high temperature and high salinity reservoirs - Jirui Zou; Xiangan Yue; Junbin Zhang; Joseph Y. Fu; Jie He; Bin Kong; Qing Ling (Arabian Journal of Geosciences, 2018)

Simulated differences in 21st century aridity due to different scenarios of greenhouse gases and aerosols - L. Lin; A. Gettelman; Q. Fu; Y. Xu (Climatic Change, 2018)

Spike densities of the amygdala and neocortex reflect progression of kindled motor seizures - Yu-Lin Wang; Sheng-Fu Liang; Alvin W. Y. Su; Fu-Zen Shaw (Medical & Biological Engineering & Computing, 2018)

Car8 dorsal root ganglion expression and genetic regulation of analgesic responses are associated with a cis-eQTL in mice - Roy C. Levitt; Gerald Y. Zhuang; Yuan Kang; Diana M. Erasso; Udita Upadhyay; Mehtap Ozdemir; Eugene S. Fu; Konstantinos D. Sarantopoulos; Shad B. Smith; William Maixner; Luda Diatchenko; Eden R. Martin; et al. (Mammalian Genome, 2017)

Enhancement of Energy Production of the Intervertebral Disc by the Implantation of Polyurethane Mass Transfer Devices - Yu-Fu Wang; Howard B. Levene; Weiyong Gu; C. -Y. Charles Huang (Annals of Biomedical Engineering, 2017)

Reservoir characteristics and methane adsorption capacity of the Upper Triassic continental shale in Western Sichuan Depression, China - Y. C. Liu; D. X. Chen; N. S. Qiu; Y. Wang; J. Fu; Y. Huyan; J. K. Jia; H. Wu (Australian Journal of Earth Sciences, 2017)

Linking Oceanic Tsunamis and Geodetic Gravity Changes of Large Earthquakes - Yuning Fu; Y. Tony Song; Richard S. Gross (Pure and Applied Geophysics, 2017)

Alterations in mechanical properties of the patellar tendon is associated with pain in athletes with patellar tendinopathy - W. C. Lee; Z. J. Zhang; L. Masci; G. Y. F. Ng; Siu Ngor Fu (European Journal of Applied Physiology, 2017)

A GCM investigation of impact of aerosols on the precipitation in Amazon during the dry to wet transition - Yu Gu; K. N. Liou; J. H. Jiang; R. Fu; Sarah Lu; Y. Xue (Climate Dynamics, 2017)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Fast neutron-induced structural rearrangements at a soybean NAP1 locus result in gnarled trichomes - Benjamin W. Campbell; Anna N. Hofstad; Suma Sreekanta; Fengli Fu; Thomas J. Y. Kono; Jamie A. O’Rourke; Carroll P. Vance; Gary J. Muehlbauer; Robert M. Stupar (Theoretical and Applied Genetics, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Abrp, a new gene, confers reduced susceptibility to tetracycline, glycylcine, chloramphenicol and fosfomycin classes in Acinetobacter baumannii - X. Li; J. Quan; Y. Yang; J. Ji; L. Liu; Y. Fu; X. Hua; Y. Chen; B. Pi; Y. Jiang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Effect of Selenium Against Lead-Induced Damage on the Gene Expression of Heat Shock Proteins and Inflammatory Cytokines in Peripheral Blood Lymphocytes of Chickens - G.X. Sun; Y. Chen; C. P. Liu; S. Li; J. Fu (Biological Trace Element Research, 2016)

Characterization of pollution transport into Texas using OMI and TES satellite, GIS and in situ data, and HYSPLIT back trajectory analyses: implications for TCEQ State Implementation Plans - D. Bella; J. Culpepper; J. Khaimova; N. Ahmed; Adam Belkalai; I. Arroyo; J. Andrews; S. Gentle; S. Emmanuel; M. Lahmouh; J. Ealy; Zayna King; et al. (Air Quality, Atmosphere & Health, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Development of roughness updating based on artificial neural network in a river hydraulic model for flash flood forecasting - J C Fu; M H Hsu; Y Duann (Journal of Earth System Science, 2016)

Meta-analyses of structural regional cerebral effects in type 1 and type 2 diabetes - Calum D. Moulton; Sergi G. Costafreda; Paul Horton; Khalida Ismail; Cynthia H. Y. Fu (Brain Imaging and Behavior, 2015)

Effects of habitual loading on patellar tendon mechanical and morphological properties in basketball and volleyball players - Z. J. Zhang; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2015)

Scale dependence of the beta diversity-scale relationship - Y. Zhang; K. Ma; M. Anand; W. Ye; B. Fu (Community Ecology, 2015)

Efficiency and Accuracy Verification of the Explicit Numerical Manifold Method for Dynamic Problems - X. L. Qu; Y. Wang; G. Y. Fu; G. W. Ma (Rock Mechanics and Rock Engineering, 2015)

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

Accuracy and Reproducibility of Patient-Specific Hemodynamic Models of Stented Intracranial Aneurysms: Report on the Virtual Intracranial Stenting Challenge 2011 - S. Cito; A. J. Geers; M. P. Arroyo; V. R. Palero; J. Pallarés; A. Vernet; J. Blasco; L. San Román; W. Fu; A. Qiao; G. Janiga; Y. Miura; et al. (Annals of Biomedical Engineering, 2015)

A novel fish cell line derived from the brain of Chinese perch Siniperca chuatsi : development and characterization - X. Fu; N. Li; Y. Lai; X. Luo; Y. Wang; C. Shi; Z. Huang; S. Wu; J. Su (Journal of Fish Biology, 2015)
In this study, a continuous cell line (named as CPB ) was established from Siniperca chuatsi brain and has been subcultured >140 times. CPB cell line predominantly consisted of fibroblast‐like cells that could grow better in Leibovitz's L‐15 supplemented with 10% foetal bovine serum at 28° C. Polymerase chain reaction amplification of 18s recombinant (r)RNA confirmed the origin of this cell line from S. chuatsi . The CPB cell line was cryopreserved at different passage levels and revived successfully with 80–90% survival. The cell line was further characterized by chromosome number and transfection. The CPB cells were highly susceptible to infectious spleen and kidney necrosis virus ( ISKNV ) with a titre of 6·58–6·62 log TCID 50 ml −1 and numerous ISKNV particles were observed in the cytoplasm by transmission electron microscopy. At the same time, ISKNV infection was confirmed by reverse transcriptase polymerase chain reaction, immunodot blot and individual challenge experiments. The development and characterization of a new brain cell line from S. chuatsi were described in this study and it could be used as an in vitro tool for propagation of ISKNV and gene expression studies.

Effect of the invasive bivalve Mytilopsis sallei on the macrofaunal fouling community and the environment of Yundang Lagoon, Xiamen, China - L.-Z. Cai; J.-S. Hwang; H.-U. Dahms; S.-J. Fu; Y. Zhuo; T. Guo (Hydrobiologia, 2014)

Quantitative trait analysis of flowering time in spring rapeseed (B. napus L.) - Y. X. Luo; C. Y. Luo; D. Z. Du; Z. Fu; Y. M. Yao; C. C. Xu; H. S. Zhang (Euphytica, 2014)

Field Evaluation of Different Wavelengths Light-Emitting Diodes as Attractants for Adult Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - L X Zheng; Y Zheng; W J Wu; Y G Fu (Neotropical Entomology, 2014)

Eukaryotic elongation factor-2 kinase (eEF2K): a potential therapeutic target in cancer - L. L. Fu; T. Xie; S. Y. Zhang; B. Liu (Apoptosis, 2014)

Oncogenic and tumor suppressive roles of microRNAs in apoptosis and autophagy - Y. Chen; L. L. Fu; X. Wen; B. Liu; J. Huang; J. H. Wang; Y. Q. Wei (Apoptosis, 2014)

Prevalence of carbapenem-hydrolyzing class D β-lactamase genes in Acinetobacter spp. isolates in China - S. Ji; Y. Chen; Z. Ruan; Y. Fu; J. Ji; Y. Fu; H. Wang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - M. J. Barbetti; S. K. Banga; T. D. Fu; Y. C. Li; D. Singh; S. Y. Liu; X. T. Ge; S. S. Banga (Euphytica, 2014)

Erratum to: Coralslurrinella hongkonensis gen. nov., sp. nov., a novel bacterium in the family Psychromonadaceae, isolated from the coral Platygyra carnosus - Yanxia Li; Yuki Chan; Yingnan Fu; Rui Zhang; Jill M. Y. Chiu (Antonie van Leeuwenhoek, 2014)

Coralslurrinella hongkonensis gen. nov., sp. nov., a novel bacterium in the family Psychromonadaceae, isolated from the coral Platygyra carnosus - Yanxia Li; Yuki Chan; Yingnan Fu; Rui Zhang; Jill M. Y. Chiu (Antonie van Leeuwenhoek, 2013)

Study on elastic P-wave propagation law in unfavorable geologic structures with discontinuous deformation analysis method - Y. H. Zhang; X. D. Fu; Q. Sheng; X. L. Leng (Arabian Journal of Geosciences, 2013)

A Factorial-based Dynamic Analysis Method for Reservoir Operation Under Fuzzy-stochastic Uncertainties - D. Z. Fu; Y. P. Li; G. H. Huang (Water Resources Management, 2013)

Isolation and characterization of 25 novel polymorphic microsatellite markers from grass carp (Ctenopharyngodon idella) - D. Li; Y. B. Shen; J. J. Fu; J. L. Li (Conservation Genetics Resources, 2013)

Distribution of platinum-group elements in magmatic and altered ores in the Jinchuan intrusion, China: an example of selenium remobilization by postmagmatic fluids - Hazel M. Prichard; Robert D. Knight; Peter C. Fisher; Iain McDonald; Mei-Fu Zhou; Christina Y. Wang (Mineralium Deposita, 2013)

Tai Chi practitioners have better postural control and selective attention in stepping down with and without a concurrent auditory response task - Xi Lu; Ka-Chun Siu; Siu N. Fu; Christina W. Y. Hui-Chan; William W. N. Tsang (European Journal of Applied Physiology, 2013)

Sequence organization and evolutionary dynamics of Brachypodium-specific centromere retrotransposons - L. L. Qi; J. J. Wu; B. Friebe; C. Qian; Y. Q. Gu; D. L. Fu; B. S. Gill (Chromosome Research, 2013)

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) - H Zhou; W J Wu; F P Zhang; Y G Fu (Neotropical Entomology, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Characteristics, loss and gain of atmospheric carbonyl compounds in winters of 2008–2010 in Pearl River Delta region, China - Yonglin Liu; Xinhui Bi; L. Y. Chan; Sheng Wen; Xinming Wang; Guoying Sheng; Jiamo Fu (Journal of Atmospheric Chemistry, 2013)

A New Vector for Identification of Prokaryotes and Their Variable-Size Genomes - Tao Hou; Fu Liu; Caixia X. Lin; Dingyuan Y. Li (Current Microbiology, 2013)

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

Hydrocarbon- and ore-bearing basinal fluids: a possible link between gold mineralization and hydrocarbon accumulation in the Youjiang basin, South China - X. X. Gu; Y. M. Zhang; B. H. Li; S. Y. Dong; C. J. Xue; S. H. Fu (Mineralium Deposita, 2012)

Correlation between plasma amino acid profiles and the various stages of hepatitis B infection - J. Yang; J. He; H. Cao; X. Zhao; S. Fu; H. Lu; Y. Chen; X. Pan; L. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Effects of Tai Chi on pre-landing muscle response latency during stepping down while performing a concurrent mental task in older adults - William W. N. Tsang; Christina W. Y. Hui-Chan; Siu N. Fu (European Journal of Applied Physiology, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

Molecular cloning, characterization and expression analysis of B cell translocation gene 1 in grass carp Ctenopharyngodon idella - Y. J. Fu; F. G. Huang; T. Yuan; J. R. Gu; G. Q. Luo; H. Xu (Journal of Fish Biology, 2012)
An expressed sequence tag (EST) of B cell translocation gene (BTG) 1 ( gcbtg1 ) was obtained from a grass carp Ctenopharyngodon idellus intestinal complementary (c)DNA library and the full‐length cDNA sequence was acquired by rapid amplification of cDNA ends (RACE) technology. The predicted Gcbtg1 protein contains the box A and box B motifs which characterized the BTG and transducer of ERBB2 (TOB) family. Multiple alignment analysis reveals that Gcbtg1 shares an overall identity of 65–94% with Gcbtg1s of other vertebrates. Real‐time quantitative PCR analysis reveals that the highest expression level of gcbtg1 was detected in liver and the lowest in muscle. Western blotting analysis indicates that the immunological cross‐reactivity occurs between C. idella and human Homo sapiens BTG1 protein. A 1008 bp 5′‐flanking region sequence was cloned and analysed.

A pre-operational three Dimensional variational data assimilation system in the North/Baltic Sea - S. Y. Zhuang; W. W. Fu; J. She (Ocean Science, 2011)
This paper describes the implementation and evaluation of a pre-operational three dimensional variational (3DVAR) data assimilation system for the North/Baltic Sea. Univariate analysis for both temperature and salinity is applied in a 3DVAR scheme in which the horizontal component of the background error covariance is modeled by an isotropic recursive filter (IRF) and the vertical component is represented by dominant Empirical Orthogonal Functions (EOFs). Observations of temperature and salinity (T/S) profiles in the North/Baltic Sea are assimilated in the year of 2005. Effect of the 3DVAR scheme is assessed by a comparison between data assimilation run and control run. The statistical analysis indicates that the model simulation is significantly improved with the 3DVAR scheme. On average, the root mean square errors (RMSE) of temperature and salinity are reduced by 0.2 °C and 0.25 psu in the North/Baltic Sea. In addition, the bias of temperature and salinity is also decreased by 0.1 °C and 0.2 psu, respectively. Starting from an analyzed initial state, one month simulation without assimilation is carried out with the aim of examining the persistence of the initial impact. It is shown that the assimilated initial state can impact the model simulation for nearly two weeks. The influence on salinity is more pronounced than temperature.

Erratum to: Genetic analysis of Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Tao Yu; Sei-Ichi Matsui; Li Zhang; Dawei Fu; Annie Pao; Alberto C. Costa; Katheleen J. Gardiner; John K. Cowell; Norma J. Nowak; Michael S. Parmacek; et al. (Human Genetics, 2011)

Genetic analysis of Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Tao Yu; Sei-Ichi Matsui; Li Zhang; Dawei Fu; Annie Pao; Alberto C. Costa; Katheleen J. Gardiner; John K. Cowell; Normal J. Nowak; Michael S. Parmacek; et al. (Human Genetics, 2011)

A new carotenoid glycoside from Rehmannia glutinosa - Guang-Miao Fu; She-Po Shi; Fanny C.F. Ip; Hai-Hong Pang; Nancy Y. Ip (Natural Product Research, 2011)

Low-level Taekwondo practitioners have better somatosensory organisation in standing balance than sedentary people - Hio-Teng Leong; Siu N. Fu; Gabriel Y. F. Ng; William W. N. Tsang (European Journal of Applied Physiology, 2011)

Hat, shade, long sleeves, or sunscreen? Rethinking US sun protection messages based on their relative effectiveness - Eleni Linos; Elizabeth Keiser; Teresa Fu; Graham Colditz; Suephy Chen; Jean Y. Tang (Cancer Causes & Control, 2011)

Human insulin gene expressing with Bombyx mori multiple nucleopolyhedrovirus (BmMNPV) expression system - Wan-fu Yue; Fang Zhou; Jia-biao Hu; Enoch Y. Park; Joe Hull; Yun-gen Miao (World Journal of Microbiology and Biotechnology, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Association of facial skin aging and vitamin D levels in middle-aged white women - Anne Lynn S. Chang; Teresa Fu; Omar Amir; Jean Y. Tang (Cancer Causes & Control, 2010)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize - Y. Z. Wang; J. Z. Li; Y. L. Li; M. G. Wei; X. H. Li; J. F. Fu (Euphytica, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Vertical Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Soil Cores Taken from a Typical Electronic Waste Polluted Area in South China - Z. Z. Yang; Y. F. Li; Y. X. Hou; H. Y. Liang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Tissue Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Captive Domestic Pigs, Sus scrofa, from a Village Near an Electronic Waste Recycling Site in South China - Y. F. Li; Z. Z. Yang; C. H. Wang; Z. J. Yang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Co-location of seed oil content, seed hull content and seed coat color QTL in three different environments in Brassica napus L. - X. Y. Yan; J. N. Li; F. Y. Fu; M. Y. Jin; L. Chen; L. Z. Liu (Euphytica, 2009)

Influence of dent corn genetic backgrounds on QTL detection for plant-height traits and their relationships in high-oil maize - M. Wei; J. Fu; X. Li; Y. Wang; Y. Li (Journal of Applied Genetics, 2009)

Differential expression of candidate genes for lignin biosynthesis under drought stress in maize leaves - Y. Hu; W. Ch. Li; Y. Q. Xu; G. J. Li; Y. Liao; F. -L. Fu (Journal of Applied Genetics, 2009)

Dent corn genetic background influences QTL detection for grain yield and yield components in high-oil maize - Y. L. Li; X. H. Li; J. Z. Li; J. F. Fu; Y. Z. Wang; M. G. Wei (Euphytica, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Co-localization of hyperphosphorylated tau and caspases in the brainstem of Alzheimer’s disease patients - Maria Sen Mun Wai; Yong Liang; Chun Shi; Eric Y. P. Cho; Hsiang-fu Kung; David T. Yew (Biogerontology, 2009)

Lipid rafts play an important role in the vesicular stomatitis virus life cycle - W. Wang; Y. J. Fu; Y. G. Zu; N. Wu; J. Reichling; T. Efferth (Archives of Virology, 2009)

Composition, Distribution, and Characterization of Polycyclic Aromatic Hydrocarbons in Soil in Linfen, China - S. Fu; H. X. Cheng; Y. H. Liu; X. J. Xia; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Reduced swimming abilities in fast‐growing transgenic common carp Cyprinus carpio associated with their morphological variations - D. Li; W. Hu; Y. Wang; Z. Zhu; C. Fu (Journal of Fish Biology, 2009)
Critical swimming speeds ( U crit ) and morphological characters were compared between the F 4 generation of GH‐transgenic common carp Cyprinus carpio and the non‐transgenic controls. Transgenic fish displayed a mean absolute U crit value 22·3% lower than the controls. Principal component analysis identified variations in body shape, with transgenic fish having significantly deeper head, longer caudal length of the dorsal region, longer standard length ( L S ) and shallower body and caudal region, and shorter caudal length of the ventral region. Swimming speeds were related to the combination of deeper body and caudal region, longer caudal length of the ventral region, shallower head depth, shorter caudal length of dorsal region and L S . These findings suggest that morphological variations which are poorly suited to produce maximum thrust and minimum drag in GH‐transgenic C. carpio may be responsible for their lower swimming abilities in comparison with non‐transgenic controls.

Organochlorine Pesticides in the Soil in Linfen, China - H. X. Cheng; S. Fu; Y. H. Liu; D. S. Li; J. H. Zhou; X. J. Xia (Bulletin of Environmental Contamination and Toxicology, 2008)

Polychlorinated Biphenyls Residues in the Soil in Linfen, China - S. Fu; H. Cheng; Y. Liu; L. Zhang; Z. Yang; K. Li; X. Xia; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Emission of volatile organic sulfur compounds from a heavily polluted river in Guangzhou, South China - Yanqing Sheng; Fanzhong Chen; Ying Yu; Xinming Wang; Guoying Sheng; Jiamo Fu; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Is peak postprandial oxygen consumption positively related to growth rate and resting oxygen consumption in a sedentary catfish Silurus meridionalis ? - S. J. Fu; Z. D. Cao; J. L. Peng; Y. X. Wang (Journal of Fish Biology, 2008)
The resting oxygen consumption , postprandial and post‐exercise peak oxygen consumption of 137 juvenile southern catfish Silurus meridionalis , weighing 18·5 ± 0·8 g (mean ± s . d .), were measured at 25° C to determine whether is positively related to postprandial and post‐exercise in sedentary S. meridionalis . In addition, postprandial metabolic response [ i.e. the specific dynamic action (SDA)] after a satiating meal and the growth performance as a consequence of a 3 week feeding‐growth trail were measured in 40 S. meridionalis , weighing 14·3 ± 0·2 g, at 25° C to determine whether postprandial is positively related to growth rate. Postprandial was positively correlated with , while post‐exercise was not. Both postprandial and post‐exercise were positively correlated with factorial and absolute scope. There was no significant correlation between the growth rate and postprandial in S. meridionalis . It suggested that as a sit‐and‐wait forager with low , low post‐exercise and high postprandial , the expenditure of energy for maintenance in S. meridionalis may be more closely related to digestive processes than locomotor activities.

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Annual time-series analyses of total gaseous mercury measurement and its impact factors on the Gongga Mountains in the southeastern fringe of the Qinghai-Tibetan Plateau - Wanze Zhu; Xuewu Fu; Xinbin Feng; Julia Y. Lu (Journal of Mountain Science, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Fast‐growing transgenic common carp mounting compensatory growth - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
Compensatory growth is a phase of accelerated growth apparent when favourable conditions are restored after a period of growth depression. To investigate if F 2 common ‘all‐fish’ growth hormone gene transgenic common carp ( Cyprinus carpio ) could mount compensatory growth, a 9 week study at 29° C was performed. The control group was fed to satiation twice a day throughout the experiment. The other two groups were deprived of feed for 1 or 2 weeks, respectively, and then fed to satiation during the re‐feeding period. At the end of the experiment, the live masses of fish in the deprived groups were still significantly lower than those of the controls. During the re‐feeding period, size‐adjusted mean specific growth rates and mean feed intakes were significantly higher in the deprived fish than in the controls, indicating a partial compensatory growth response in these fish. No significant differences were found in food conversion efficiency between the deprived and control fish during re‐feeding, suggesting that hyperphagia was the mechanism responsible for increased growth rates. The proximate composition of the deprived fish at the end of the experiment was similar to that of the control fish. This study is, to our knowledge, the first to report that fast‐growing transgenic fish can achieve partial compensation of growth following starvation.

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular characterization of the surface glycoprotein genes of an H5N1 influenza virus isolated from a human in Guangdong, China - J.-J. Zhou; J. Fu; D.-Y. Fang; H.-J. Yan; J. Tian; J.-M. Zhou; J.-P. Tao; Y. Liang; L.-F. Jiang (Archives of Virology, 2007)

Modulation of neural response to happy and sad faces by acute tryptophan depletion - Paolo Fusar-Poli; Paul Allen; Francis Lee; Simon Surguladze; Nigel Tunstall; Cynthia H. Y. Fu; Michael J. Brammer; Anthony J. Cleare; Philip K. McGuire (Psychopharmacology, 2007)

CO 2 control of Trichodesmium N 2 fixation, photosynthesis, growth rates, and elemental ratios: Implications for past, present, and future ocean biogeochemistry - D. A. Hutchins; F.-X. Fu; Y. Zhang; M. E. Warner; Y. Feng; K. Portune; P. W. Bernhardt; M. R. Mulholland (Limnology and Oceanography, 2007)
Diazotrophic marine cyanobacteria in the genus Trichodesmium contribute a large fraction of the new nitrogen entering the oligotrophic oceans, but little is known about how they respond to shifts in global change variables such as carbon dioxide (CO 2 ) and temperature. We compared Trichodesmium dinitrogen (N 2 ) and CO 2 fixation rates during steady‐state growth under past, current, and future CO 2 scenarios, and at two relevant temperatures. At projected CO 2 levels of year 2100 (76 Pa, 750 ppm), N 2 fixation rates of Pacific and Atlantic isolates increased 35–100%, and CO 2 fixation rates increased 15‐128% relative to present day CO 2 conditions (39 Pa, 380 ppm). CO 2 ‐mediated rate increases were of similar relative magnitude in both phosphorus (P)‐replete and P‐limited cultures, suggesting that this effect may be independent of resource limitation. Neither isolate could grow at 15 Pa (150 ppm) CO 2 , but N 2 and CO 2 fixation rates, growth rates, and nitrogen : phosophorus (N : P) ratios all increased significantly between 39 Pa and 152 Pa (1500 ppm). In contrast, these parameters were affected only minimally or not at all by a 4°C temperature change. Photosynthesis versus irradiance parameters, however, responded to both CO 2 and temperature but in different ways for each isolate. These results suggest that by the end of this century, elevated CO 2 could substantially increase global Trichodesmium N 2 and CO 2 fixation, fundamentally altering the current marine N and C cycles and potentially driving some oceanic regimes towards P limitation. CO 2 limitation of Trichodesmium diazotrophy during past glacial periods could also have contributed to setting minimum atmospheric CO 2 levels through downregulation of the biological pump. The relationship between marine N 2 fixation and atmospheric CO 2 concentration appears to be more complex than previously realized and needs to be considered in the context of the rapidly changing oligotrophic oceans.

Composition and antimicrobial activity of the essential oil of Actinidia macrosperma from China - Y. Lu†; Y. P. Zhao†; Z. C. Wang; S. Y. Chen; C. X. Fu* (Natural Product Research, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Growth and energy budget of F 2 ‘all‐fish’ growth hormone gene transgenic common carp - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
The growth and energy budget for F 2 ‘all‐fish’ growth hormone gene transgenic common carp Cyprinus carpio of two body sizes were investigated at 29·2° C for 21 days. Specific growth rate, feed intake, feed efficiency, digestibility coefficients of dry matter and protein, gross energy intake ( I E ), and the proportion of I E utilized for heat production ( H E ) were significantly higher in the transgenics than in the controls. The proportion of I E directed to waste products [faecal energy ( F E ) and excretory energy loss ( Z E + U E ) where Z E is through the gills and U E through the kidney], and the proportion of metabolizable energy ( M E ) for recovered energy ( R E ) were significantly lower in the transgenics than in the controls. The average energy budget equation of transgenic fish was as follows: 100 I E = 19·3 F E + 6·0 ( Z E + U E ) + 45·2 H E + 29·5 R E or 100 M E = 60·5 H E + 39·5 R E . The average energy budget equation of the controls was: 100 I E = 25·2 F E + 7·4 ( Z E + U E ) + 35·5 H E + 31·9 R E or 100 M E = 52·7 H E + 47·3 R E . These findings indicate that the high growth rate of ‘all‐fish’ transgenic common carp relative to their non‐transgenic counterparts was due to their increased feed intake, reduced lose of waste productions and improved feed efficiency. The benefit of the increased energy intake by transgenic fish, however, was diminished by their increased metabolism.

Octad pollen formation in Cymbopetalum (Annonaceae): the binding mechanism - C. -H. Tsou; Y. -L. Fu (Plant Systematics and Evolution, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Effect of acute tryptophan depletion on pre-frontal engagement - Paul P. Allen; Anthony J. Cleare; Francis Lee; Paolo Fusar-Poli; Nigel Tunstall; Cynthia H. Y. Fu; Micheal J. Brammer; Philip K. McGuire (Psychopharmacology, 2006)

Genetic analyses and mapping of a new thermo-sensitive genic male sterile gene in maize - J. H. Tang; Z. Y. Fu; Y. M. Hu; J. S. Li; L. L. Sun; H. Q. Ji (Theoretical and Applied Genetics, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Removal of Cu2+ and dye from wastewater using the heavy metal precipitant N,N-bis-(dithiocarboxy)piperazine - F. L. Fu; Q. R. Xuan; R. M. Chen; Y. Xiong (Environmental Chemistry Letters, 2006)

Targeting xa13, a recessive gene for bacterial blight resistance in rice - Zhaohui Chu; Binying Fu; Hong Yang; Caiguo Xu; Zhikang Li; A. Sanchez; Y. J. Park; J. L. Bennetzen; Qifa Zhang; Shiping Wang (Theoretical and Applied Genetics, 2006)

QTLs for drought escape and tolerance identified in a set of random introgression lines of rice - J. L. Xu; H. R. Lafitte; Y. M. Gao; B. Y. Fu; R. Torres; Z. K. Li (Theoretical and Applied Genetics, 2005)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

Mercury Accumulation and Distribution in Medaka after the Exposure to Sublethal Levels of Methylmercury - C.-Y. Liao; Q.-F. Zhou; J.-B. Shi; J.-J. Fu; G.-B. Jiang (Bulletin of Environmental Contamination and Toxicology, 2005)

Tryptophan depletion reduces right inferior prefrontal activation during response inhibition in fast, event-related fMRI - Katya Rubia; Francis Lee; Anthony J. Cleare; Nigel Tunstall; Cynthia H. Y. Fu; Michael Brammer; Phillip McGuire (Psychopharmacology, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Analyses of cis -acting elements that affect the transposition of Mos1 mariner transposons in vivo - D. W. Pledger; Y. Q. Fu; C. J. Coates (Molecular Genetics and Genomics, 2004)

Molecular diversity and multilocus organization of the parental lines used in the International Rice Molecular Breeding Program - S. B. Yu; W. J. Xu; C. H. M. Vijayakumar; J. Ali; B. Y. Fu; J. L. Xu; Y. Z. Jiang; R. Marghirang; J. Domingo; C. Aquino; S. S. Virmani; Z. K. Li (Theoretical and Applied Genetics, 2003)

Present-day crustal deformation in China relative to ITRF97 kinematic plate model - Y. Fu; W. Zhu; X. Wang; W. Duan; X. Wu; W. Jiao (Journal of Geodesy, 2002)

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

CDK inhibitors suppress apoptosis induced by chemicals and by excessive expression of a cell death gene, reaper, in Drosophila cells - M. Nagano; K. Ui-Tei; H. Suzuki; Zheng-fu Piao; Y. Miyata (Apoptosis, 2000)

Effectiveness of bulking procedures in measuring population-pairwise similarity with dominant and co-dominant genetic markers - Y. B. Fu (Theoretical and Applied Genetics, 2000)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Incomplete Block Designs for Genetic Testing: Statistical Efficiencies with Missing Observations - Yong-Bi Fu; Alvin D. Yanchuk; Gene Namkoong; G. Peter Y. Clarke (Forest Science, 1999)
Missing observations are common in forest genetic field trials and are expected to reduce statistical efficiencies of any applied field designs. Such reductions could lower the presumed efficiency and other benefits of implementing any incomplete block designs (ICBs). In this study, we addressed this by computer simulation of a full-sib progeny trial with up to 20% of the observations missing. Four scenarios of missing observations (random, row, column, and genetic mortality) and tests of both clones and seedling families were examined. Two types of ICBs (alpha and no constraint) with single-tree plots, and their corresponding randomized complete block design (RCB), were considered on test sites with gradient and patchy environmental variation. Our simulations show that: (1) the statistical efficiencies of estimating family (or clone) means with both ICB and RCB were very sensitive to the percentage, not the scenarios, of missing observations examined; (2) the statistical efficiencies for both ICB and RCB were reduced as the number of missing observations increased, except in the cases of clonal genetic mortality; (3) the relative efficiency of ICB over RCB (at equal levels of missing observations) was reduced slightly as the level of missing observations increased; (4) the relative efficiencies for the seedling family tests were a little more sensitive to the levels of missing observations than those for the clonal tests, and; (5) the two ICBs showed little variation in the relative efficiencies across the missing observation scenarios and test conditions examined. Implications of these results for forest genetic field trials are discussed. For. Sci. 45(3):374-380.

Three-dimensional organization and dynamic changes of the actin cytoskeleton in embryo sacs ofZea mays andTorenia fournieri - B. -Q. Huang; Y. Fu; S. Y. Zee; P. K. Hepler (Protoplasma, 1999)

Patterns of the purging of deleterious genes with synergistic interactions in different breeding schemes - Y. B. Fu (Theoretical and Applied Genetics, 1999)

Studies on somaclonal variation in Phalaenopsis - W. H. Chen; T. M. Chen; Y. M. Fu; R. M. Hsieh; W. S. Chen (Plant Cell Reports, 1998)

Growth and feed utilization by F 4 human growth hormone transgenic carp fed diets with different protein levels - C. Fu; Y. Cui; S. S. O. Hung; Z. Zhu (Journal of Fish Biology, 1998)
The F 4 generation of human growth hormone (hGH) transgenic red common carp Cyprinus carpio had significantly higher growth rates than the non‐transgenic controls. Protein and energy intakes were significantly higher in the transgenic carp than in the controls fed the 20% protein diet, but were not different between the two strains fed diets with 30 and 40% protein. Faecal protein loss, as a proportion of protein intake, was significantly lower in the transgenics than in the controls fed diets with 20 and 30% protein, but was not different between the two strains fed diet with 40% protein. Faecal energy loss, as a proportion of energy intake, was significantly lower in the transgenics than in the controls fed diet with 20% protein, but was not different between the two strains fed diets with 30 and 40% protein. Recovered protein, as a proportion of protein intake, was significantly higher in the transgenics than in the controls fed all diets, whereas recovered energy was significantly higher in the transgenic fish fed the 40% protein diet. For fish fed each diet, the transgenics had significantly higher body contents of dry matter and protein, but lower contents of lipid than the controls. It was concluded that transgenics were more efficient in utilizing dietary protein than the controls. At a lower dietary protein level, transgenics achieved higher growth rates mainly by increasing feed intake; at higher levels of dietary protein, transgenics achieved higher growth rates mainly through a higher energy conversion efficiency.

Receptive field properties of visual neurons in the avian nucleus lentiformis mesencephali - Y.-X. Fu; Hong-Feng Gao; M.-W. Guo; S.-R. Wang (Experimental Brain Research, 1998)

Angiotensin II receptors: Localization of type I and type II in rat epididymides of different developmental stages - P. S. Leung; H. C. Chan; L. X. M. Fu; P. Y. Leung; S. B. C. Chew; P. Y. D. Wong (The Journal of Membrane Biology, 1997)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

Background exposure of urban populations to lead and cadmium: comparison between China and Japan - Y.-Q. Wu; Zuo-Wen Zhang; Chan-Seok Moon; Shinichro Shimbo; Takao Watanabe; Feng-Sheng He; Shun-Fu Zhou; Jiang-Bin Qu; M. Ikeda; De-Ming Su (International Archives of Occupational and Environmental Health, 1997)

The cellular and molecular basis of peripheral nerve regeneration - Susan Y. Fu; Tessa Gordon (Molecular Neurobiology, 1997)

Determination of thein situ forces and force distribution within the human anterior cruciate ligament - Glen A. Livesay; Hiromichi Fujie; Shinji Kashiwaguchi; Duane A. Morrow; Freddie H. Fu; Savio L. -Y. Woo (Annals of Biomedical Engineering, 1995)